POLICE NON-COMPLIANCE AND CONSTITUTIONAL DISOBEDIENCE IN INDONESIA - Muthahhar Datau; Erman I. Rahim; Supriyadi A Arief (Journal of Governance and Law Reform, 2026)
This study aims to analyze the legal consequences of the Indonesian National Police’s non-compliance with Constitutional Court Decision No. 114/PUU-XXIII/2025 and to examine its implications for Indonesia’s constitutional system. The decision prohibits active members of the Indonesian National Police from holding civilian positions unless they resign or retire from police service. However, several provisions of Regulation of the Indonesian National Police No. 10 of 2025 are considered inconsistent with the Constitutional Court’s ruling, thereby creating a legal antinomy and uncertainty in its implementation. This study employs a normative legal research method using statutory and conceptual approaches. The analysis focuses on the hierarchy of laws and regulations, the final and binding nature of Constitutional Court decisions, and the constitutional limits of authority among state institutions. Legal materials were examined qualitatively through legal interpretation and systematic analysis. The results indicate that non-compliance with the Constitutional Court’s decision may constitute constitutional disobedience, weaken the supremacy of the Constitution, and create legal uncertainty regarding the appointment of active police officers to civilian positions. It also undermines the authority of the Constitutional Court and disrupts the checks and balances mechanism. The study concludes that regulatory harmonization, stricter institutional supervision, and an effective enforcement mechanism are required to ensure compliance with Constitutional Court decisions.